Fixation or inspiration? A meta-analytic review of the role of examples on design processes. (July 2015) - Sio, Ut Na; Kotovsky, Kenneth; Cagan, Jonathan
Abstract : A meta-analytical review of design studies ( N = 43) was conducted examining whether and under what conditions the presence of examples will induce fixation or inspiration. The analysis revealed that providing examples made individuals generate more example-related and fewer categories of ideas, however, the ideas produced were more novel. Also, the quality of solutions ideas was positively correlated with the degree of copying from examples. The facilitatory effects on novelty and quality increased when fewer and less common examples were presented. Presenting a single and uncommon example may encourage individuals to shift from traversing between different parts of the problem space to conducting a deeper search in a specific and remote domain, facilitating the generation of high-quality and novel ideas. Highlights: We conducted a meta-analysis of studies examining the effect of examples on design. Examples led individuals to explore the problem space more narrowly and deeply. The presence of example reduced the variety of the design solution ideas. The presence of example improved the novelty and quality of the solution ideas. Providing one single and uncommon example facilitated the design processes most.